The Existence Of Kenthongan As Folk Art: Study Of Kenthongan Banyumas - Muchsin, Ibnu Amar (Universitas Negeri Semarang, 2021)
Since its appearance until now, Kenthongan is still exist and its journey has changed its function, from a means of communication to become a folk art. Banyumas is an area that has a lot of bamboo plants as materials for making Kenthongan which has the potential for development. Kenthongan art in Banyumas exists and develops until now. Therefore, the purpose of this study is to identify and explain the existence of Kenthongan as a folk art in the Banyumas. This research is a qualitative descriptive study with an ethnomusicological approach. Kenthongan as a cultural product (living tradition) has been present as a folk art since its inception, having the form of a slit-drum and developing into a non-slit-drum. The development of the non-slit-drum form is an adaptation of Gambang Calung Banyumas’ blade. Kenthongan non-slit-drum developed in three stages, namely 1) in 2002, 2) in 2005 and 3) in 2013. Its development includes the form and the function of which it was originally a rhythmic instrument in 2002-2005 developed into a melodic instrument in 2013.